2018
DOI: 10.22159/ajpcr.2018.v11s2.28591
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Assessment of in Vitro Antimicrobial Activity of Curcuma Caesia Roxb. And Curcuma Amada Roxb

Abstract: Objective: The aim of the present study was to compare the in vitro antimicrobial activity of Curcuma caesia Roxb. and Curcuma amada Roxb. family Zingiberaceae. Both plants have been used traditionally for curing a number of diseases and ailments. The plants have been specifically used in skin problems and inflammatory conditions. Methods: Each plant material was extracted with dichloromethane (DCM) and ethanol. All extracts were subjected to preliminary phytochemical screening. The antibacterial activity of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The resistance shown by E.coli could be attributed to its cell wall structure as it has an effective permeability barrier, comprised of a thin lipopolysaccharide exterior membrane, which could restrict the penetration of the plant extract. A similar study showed that the zone of inhibition of ethanol C. caesia extract on E.coli at 100mg/ml produced zone of inhibition 12mm which was least effective (Kaur et al, 2018). Despite being ineffective against E.coli, the ethanolic extract of this plant showed the maximum zone of inhibition of 22mm at concentration 200mg/ml against S. aureus.…”
Section: Antimicrobial Activity Of Samples Extractsmentioning
confidence: 83%
“…The resistance shown by E.coli could be attributed to its cell wall structure as it has an effective permeability barrier, comprised of a thin lipopolysaccharide exterior membrane, which could restrict the penetration of the plant extract. A similar study showed that the zone of inhibition of ethanol C. caesia extract on E.coli at 100mg/ml produced zone of inhibition 12mm which was least effective (Kaur et al, 2018). Despite being ineffective against E.coli, the ethanolic extract of this plant showed the maximum zone of inhibition of 22mm at concentration 200mg/ml against S. aureus.…”
Section: Antimicrobial Activity Of Samples Extractsmentioning
confidence: 83%
“…From Table 1 it was concluded that, chloroform, ethanol, methanol and distilled water extracts were gave good results for terpenoid, cardiac glycosides and gum (Singh and Phucho, 2015) positive results for tannins in ethanol, methanol and distilled water (Singh and Phucho, 2015). (Kaur et al, 2018)revealed the presence of carbohydrates, saponins, glycosides, phytosterols, resins, and lavonoids in rhizome extracts. From Table 1 can conclude the rhizome extract of C.amada exhibited optimistic results for maximum therapeutic chemical constituents.…”
Section: Phytochemical Screening Of Curcuma Amadamentioning
confidence: 99%
“…The studies have shown that ethanolic extract of C. amada against various tested microorganisms was most effective compared to other phenolic extracts (acetone, chloroform, ether and carbon tetrachloride) and aqueous extract. [ 6 7 11 ]…”
Section: Discussionmentioning
confidence: 99%